Experimental Analysis and Comparative Mechanical testing on Glass- Carbon Hybrid Composites. (2019) - Poyyathappan, K.; Bhaskar, G.B.; Rajesh, S.; Pazhanivel, K.
Abstract: This paper deals with the fabrication of Glass fiber reinforced plastic (GFRP), Carbon fiber reinforced plastic (CFRP), Glass-Carbon fiber reinforced plastic (G-CFRP), Carbon-Glass fiber reinforced plastic (C-GFRP) and starting glass and ending carbon reinforced composite laminates (G-C-G-CFRP) that have been organized using hand layup techniques. Test specimens were prepared by using numerous composite materials as per ASTM standards. The mechanical properties which include tensile, flexural, impact, shear and hardness strength of diverse composites have been evaluated and compared. The CFRP are best suited for flexural and tensile test and for impact test, shear test and hardness test hybrid composite is found to be higher than others.